Diversified livelihoods through effective agro-enterprise interventions: Creating a cumulative learning framework between CIAT and development NGOs in Central America. - Lundy, Mark M. (International Center for Tropical Agriculture, 2008)
This report provides a summary of the learning alliance project. Starting in 2003, a group of actors in Central America including International and local NGOs, an international agricultural research center, a national university and the International Development Research Centre came together to explore how to improve the links between research and development actors through learning alliances. For research partners, learning alliances have allowed the development of stronger networks with end users. These links provide clear orientation and feedback on key areas for further research, a potential platform to present additional action research proposals, reduced transactions costs in proposal development and project implementation and access to complementary funding sources including the sale of services to development partners and projects. An additional gain is the capacity to offer a credible multi-sector learning platform for more systemic proposals. Proposals that contain a critical mass of R & D actors are more attractive to both donor agencies as well as potential public and private sector partners.